Utilization of superparamagnetic iron oxide nanoparticles (SPIONs) impregnated activated carbon for removal of hexavalent chromium - Farhana, Aisha; Selvarani, A. Jenifer; Samrot, Anthony V.; Alsrhani, Abdullah; Mok, Pooi Ling (Hindawi Limited, 2022)
Chromium (Cr) is a toxic heavy metal present in industrial effluent which could cause degenerative diseases on ingestion. Therefore, elimination of Cr from contaminated water becomes essential to preserve and sustain the quality of life. In this study, superparamagnetic iron oxide nanoparticles (SPIONs) were impregnated on activated carbon and checked for enhanced removal of Cr(VI). Thus, granular activated carbon (N-GAC) of mesh size 8 ∗ 20 was impregnated with SPIONs to produce SPIONs impregnated activated carbon (Sp-GAC) and characterized using UV-VIS spectrophotometer, FT-IR, SEM-EDX, XRD, and VSM. Sp-GAC was found to be possessing superparamagnetic behavior, and it was used in batch adsorption study where the adsorption parameters like pH, concentration of adsorbent, and adsorbent-adsorbate were optimized. It was found that Cr(VI) adsorption was predominant at acidic pH (pH 3) for both cases; moreover, N-GAC showed better adsorption comparatively. Both the N-GAC and Sp-GAC adsorption were found to be obeying to Langmuir.